Comparison of the impact of oral versus transdermal estrogen on serum lipoproteins - (:unkn) unknown (My University, 1994)
In an attempt to compare the effects of transdermal and oral conjugated estrogen on serum lipoproteins, 35 premenopausal women who underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy were randomized to receive either 0.625 mg of conjugated oral estrogen or 0.05 mg transdermal 17 beta-E2 during the first postoperative year. Lipid profiles were assessed before surgery and at 3, 6, 9, and 12 months of therapy in each subject. Neither oral nor transdermal estrogen replacement therapy produced significant changes on serum lipoproteins at the end of first year when compared with baseline preoperative values. We conclude that both transdermal and oral administration of estrogen are promising in the maintenance of premenopausal lipid values after menopause.
Keywords: Adult; Female; Humans; Middle Aged; Estrogen Replacement Therapy; Administration, Oral; Triglycerides; Administration, Cutaneous; Estradiol; Lipoproteins; Cholesterol, LDL; Ovariectomy; Hysterectomy; Cholesterol, HDL; Cholesterol, VLDL